2017
DOI: 10.18869/acadpub.jafm.73.241.27628
|View full text |Cite
|
Sign up to set email alerts
|

Air Entrainment in High Pressure Multihole Gasoline Direct Injection Sprays

Abstract: Experimental and numerical investigation of multihole gasoline direct injection (GDI) sprays at high injection pressure and temperature are performed. The primary objective of this study is to analyse the role of gas entrainment and spray plume interactions on the global spray parameters like spray tip penetration, spray angles and atomization. Three-hole 90° spray cone angle and six-hole 60° spray cone angle injectors are used for current work to examine the effect of the geometry of the injector on the spray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The distance between the injection holes is also an important parameter that play a crucial role in spray characteristics [8]. The spray characteristics based on the gas entrainment of a three hole injector is compared with 6 hole injector in [11]. It was observed that six-hole injector partially collapsed under moderate evaporating conditions while three-hole injector did not collapse.…”
Section: Injector Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the injection holes is also an important parameter that play a crucial role in spray characteristics [8]. The spray characteristics based on the gas entrainment of a three hole injector is compared with 6 hole injector in [11]. It was observed that six-hole injector partially collapsed under moderate evaporating conditions while three-hole injector did not collapse.…”
Section: Injector Designmentioning
confidence: 99%
“…However, the chamber pressures are much higher in comparison to the gasoline engine condition due the difference of compression ignition in diesel engines and spark ignition is gasoline engines. GDI sprays have been observed to show a collapsing effect under highly evaporating conditions [11,12]. The collapsing effect has been observed to be more pronounced in flash boiling conditions where the super-heated fuel causes the spray to expand instantly during the spray injection process especially under low chamber pressure [13].…”
Section: Introductionmentioning
confidence: 99%
“…By definition, flashboiling is referred to as superheated injections, whereas spray collapse is referred to as the spatial contraction of nominal spray targetings of gasoline sprays. Spray collapse can be affected or induced by flashboiling, but also be enforced at non-superheated conditions by a simple increase in the flow hole number at multihole injectors (see Lenz 44 and Khan et al 45 ). From phenomenological point of view, very often no differentiation is made and spray collapse is equalized with flashboiling.…”
Section: Jet-to-jet Interactionsmentioning
confidence: 99%
“…A recent study indicated that the difference of spray collapse cause under flashing and non-flashing conditions [8]. The subcooled spray generally became collapse under high ambient pressure conditions due to the air entrainment causing and enhancing the central low-pressure zone [9,10]. However, a recent study has considered that the massive production of vapor counteracts the low-pressure tendency, explaining the cause of flash boiling spray collapse is different to the subcooled condition [11].…”
Section: Introductionmentioning
confidence: 99%